1-deoxynojirimycin, a glycosylation inhibitor influences the expression of extracellular matrix proteins in osteosarcoma cells / Zulaika Roslan ... [et al.] - Roslan, Zulaika; Muhamad, Mudiana; Selvaratnam, Lakshmi; Ab-Rahim, Sharaniza (Universiti Teknologi MARA, Sabah, 2023)
Malignant tumour cells secrete extracellular matrix (ECM) proteins with growth factors and cytokines to promote cell motility and adhesion for metastasis. The cell-ECM adhesion sites are comprised of integrin-bound ECM proteins, which are glycoconjugates, susceptible to the aberrant glycosylation resulting in alterations of cell-ECM adhesion dynamics. Inhibition of glycosylation could decrease the rate of invasiveness in metastatic tumour cells like osteosarcoma (OS), of which the underlying mechanism is still unknown. Hence, this study aims to determine the effect of glucosidase inhibitors towards the expression of ECM proteins in metastatic OS cell lines. OS cells (MG63) were treated with 0.5 mM of 1-deoxynojirimycin (1-DNJ). Analyses such as the glycosylation assay, ECM-cell adhesion assay, scratch assay, and Western blot analysis were performed after a 24-h treatment for each respective sample. The expression level of glycosylated proteins was the highest in non-treated MG63 cells. The cell migration rate was increased in MG63 cells treated with 1-DNJ compared to the normal osteoblast cells. The cell adhesion assay results showed an increased rate of cell adhesion towards vitronectin but decreased adhesion rate towards collagen (types I, II, and IV), fibronectin, laminin, and tenascin in 1-DNJ-treated OS cells. Western blot analysis presented a high expression level of fibronectin, vitronectin, and collagen type II in both non-treated and treated groups of MG63 cells. The inhibitory effect of 1-DNJ upregulates ECM remodelling by disrupting integrin from binding to the ECM proteins, subsequently increasing the migration rate of metastatic OS cells.